Integrated Nonpharmacological Intervention for Patients with MCI—A Preliminary Study in Shanghai, China - Hui Yang; Yinghong Liu; Honglin Chen; You Yin (International Journal of Integrated Care, 2022)
Objective: Mild cognitive impairment is a transitional state between normal aging and Alzheimer’s and is an internationally recognized pre-stage state of Alzheimer’s. It is the starting point for early detection and intervention in dementia. An empirical study was conducted to determine how medical social workers provide intervention services to older adults with mild cognitive impairment, specific strategies for change, and the effectiveness of the intervention. Methods: This was a quasi-experimental intervention study. Conclusion: Through integrated intervention, the development of cognitive impairment can be significantly delayed, cognitive abilities can be improved ('p' < .05), and decline in daily living abilities can be significantly delayed ('p' < .05). At the same time, the mental health of participants can be improved to a certain extent.